Partisipasi Orang Tua dalam Kegiatan Ekstrakurikuler sebagai Upaya Pengembangan Potensi Anak - Ayunda Risky Yanti; Fitria Nadila; Siti Khodijah; Suci Ramadani Islamiyah; Rifqi Hayat Kurniawan; Rezky Rahmani; Suhaimi Suhaimi (JURNAL ILMIAH NUSANTARA, 2026)
Parental involvement is a crucial pillar in supporting a child’s educational journey. This involvement extends beyond academic achievement and plays a significant role in shaping character and uncovering hidden potential. Schools often utilize extracurricular programs as an important platform for this development, providing opportunities that go beyond the standard curriculum. Through these activities, students are able to cultivate their unique talents, creativity, and interpersonal skills. This study examines how parents engage in extracurricular environments and how such involvement influences the development of their children. Using a qualitative approach, the research reviews existing scholarly literature to explore the dynamics of parental participation in education. The findings indicate that when parents take an active role, students tend to demonstrate higher motivation, stronger self-confidence, and improved social interaction skills. Therefore, a strong partnership between families and schools is essential to ensure that every student can achieve their full potential.